Identification of novel HLA-A2-restricted human immunodeficiency virus type 1-specific cytotoxic T-lymphocyte epitopes predicted by the HLA-A2 supertype peptide-binding motif. - Altfeld, M; Livingston, B; Reshamwala, N; Nguyen, P; Addo, M; Shea, A; Newman, M; Fikes, J; Sidney, J; Wentworth, P; Chesnut, R; Eldridge, R; et al. (2001)
Virus-specific cytotoxic T-lymphocyte (CTL) responses are critical in the control of human immunodeficiency virus type 1 (HIV-1) infection and will play an important part in therapeutic and prophylactic HIV-1 vaccines. The identification of virus-specific epitopes that are efficiently recognized by CTL is the first step in the development of future vaccines. Here we describe the immunological characterization of a number of novel HIV-1-specific, HLA-A2-restricted CTL epitopes that share a high degree of conservation within HIV-1 and a strong binding to different alleles of the HLA-A2 superfamily. These novel epitopes include the first reported CTL epitope in the Vpr protein. Two of the novel epitopes were immunodominant among the HLA-A2-restricted CTL responses of individuals with acute and chronic HIV-1 infection. The novel CTL epitopes identified here should be included in future vaccines designed to induce HIV-1-specific CTL responses restricted by the HLA-A2 superfamily and will be important to assess in immunogenicity studies in infected persons and in uninfected recipients of candidate HIV-1 vaccines.